Patient-Reported Outcomes Through 1 Year of an HIV-1 Clinical Trial Evaluating Long-Acting Cabotegravir and Rilpivirine Administered Every 4 or 8 Weeks (ATLAS-2M) - Chounta, Vasiliki; Overton, Edgar T.; Mills, Anthony; Swindells, Susan; Benn, Paul D.; Vanveggel, Simon; van Solingen-Ristea, Rodica; Wang, Yuanyuan; Hudson, Krischan J.; Shaefer, Mark S.; Margolis, David A.; Smith, Kimberly Y.; et al. (The patient : patient-centered outcomes research, 2021)
Background Advances in HIV-1 therapeutics have led to the development of a range of daily oral treatment regimens, which share similar high efficacy rates. Consequently, more emphasis is being placed upon the individual’s experience of treatment and impact on quality of life. The first long-acting injectable antiretroviral therapy for HIV-1 (long-acting cabotegravir + rilpivirine [CAB + RPV LA]) may address challenges associated with oral treatment for HIV-1, such as stigma, pill burden/fatigue, drug–food interactions, and adherence. Patient-reported outcomes (PROs) collected in an HIV-1 clinical trial (ATLAS-2M; NCT03299049) comparing participants’ experience with two dosing regimens (every 4 weeks [Q4W] vs. every 8 weeks [Q8W]) of CAB + RPV LA are presented herein. Methods PRO endpoints evaluated through 48 weeks of therapy included treatment satisfaction (HIV Treatment Satisfaction Questionnaire [HIVTSQ]), treatment acceptance (“General Acceptance” domain of the Chronic Treatment Acceptance [ACCEPT ® ] questionnaire), acceptability of injections (Perception of Injection [PIN] questionnaire), treatment preference (questionnaire), and reasons for switching to/continuing long-acting therapy (exploratory endpoint; questionnaire). Participants were randomized 1:1 to receive CAB + RPV LA Q8W or Q4W. Results were stratified by prior CAB + RPV exposure in either preplanned or post hoc analyses. Results Overall, 1045 participants were randomized to the Q8W ( n = 522) and Q4W ( n = 523) regimens; 37% ( n = 391/1045) had previously received CAB + RPV in ATLAS. For participants without prior CAB + RPV exposure, large increases from baseline were reported in treatment satisfaction in both long-acting arms (HIVTSQ status version), with Q8W dosing statistically significantly favored at Weeks 24 ( p = 0.036) and 48 ( p = 0.004). Additionally, improvements from baseline were also observed in the “General Acceptance” domain of the ACCEPT questionnaire in both long-acting arms for participants without prior CAB + RPV exposure; however, no statistically significant difference was observed between arms at either timepoint (Week 24, p = 0.379; Week 48, p = 0.525). Significant improvements ( p < 0.001) in the “Acceptance of Injection Site Reactions” domain of the PIN questionnaire were observed from Week 8 to Weeks 24 and 48 in both arms for participants without prior CAB + RPV exposure. Participants with prior CAB + RPV exposure reported high treatment satisfaction (mean [HIVTSQ status version]: Q8W 62.2/66.0; Q4W 62.0/66.0), treatment acceptance (mean: Q8W 89.3/100; Q4W 91.2/100), and acceptance of injection site reactions (mean [5 = not at all acceptable; 1 = totally acceptable]: Q8W 1.72; Q4W 1.59) at baseline/Week 8 that were maintained over time. Participants without prior CAB + RPV exposure who received Q8W dosing preferred this regimen over oral CAB + RPV (98%, n = 300/306). Among those with prior Q4W exposure, 94% ( n = 179/191) preferred Q8W dosing versus Q4W dosing (3%, n = 6/191) or oral CAB + RPV (2%, n = 4/191). Conclusions Both long-acting regimens provided high treatment satisfaction and acceptance, irrespective of prior CAB + RPV exposure, with most participants preferring Q8W dosing over both the Q4W regimen and their previous daily oral regimen. The PRO data collected at Week 48 support the therapeutic potential of CAB + RPV LA. Funding ViiV Healthcare and Janssen. Trial Registration ATLAS-2M: ClinicalTrials.gov NCT03299049, registered October 2, 2017. Plain Language Summary Developments in HIV-1 treatment have resulted in effective daily oral medications. However, life-long pill taking can come with several challenges. These include having a daily reminder of living with HIV-1. Treatment satisfaction is important to consider when evaluating a new medicine. This is because it can affect people’s quality of life. The purpose of this study was to evaluate people’s experiences with the first long-acting injectable medicine for HIV-1. The medicine is called cabotegravir + rilpivirine long-acting (CAB + RPV LA). Over approximately 1 year, this study measured people’s satisfaction and experiences while receiving injections of CAB + RPV LA. Injections were given either every 4 weeks or every 8 weeks. The study included people who had never had CAB + RPV LA, as well as people who were already receiving CAB + RPV LA. For people new to CAB + RPV LA, their satisfaction increased compared with their previous medication. They also had improvements in their experiences of injection site reactions throughout the study. For people who were already receiving CAB + RPV LA, their high satisfaction with this treatment and tolerability of injection site reactions were maintained over time. Overall, improvements were similar between people receiving injections every 4 weeks and people receiving injections every 8 weeks. People with experience of both injection schedules tended to prefer to receive injections every 8 weeks. These results show that CAB + RPV LA can provide quality-of-life improvements for people who have HIV-1.